The history of one spectacle (Chronology and topography of „The destroyed land“) - Oniščik, Marija (Religija ir kultūra, 2007)
The text tells a story of „The Destroyed Land“ – the spectacle by Gintaras Varnas, considered as a spiral journey through time and places, paradigmatically showing the historical view of how the spectacle was born and performed, what literary images from Arthurian cycle gave rise to its plot and setting, what the historical and mythological import lies in the beginning of Grail legend, and what the sacramental meaning follows from it. The philosophical purpose of the text is to investigate the problem of time as it is presented in the spectacle together with treatment of place. It is argued that in the spectacle, there is a medieval view of history as „vertical“ time, presented paradigmatically as a whole, which reminds us of the Bergsonian conception of time with its instantaneous multiplicity. It is also proximate to medieval notion of aeviternity in Thomas Aquinas, as the mean between time and eternity, in which the succession of time treated as the changeableness of place, is compatible with being simultaneously whole. The text also analyses those features of the spectacle, which make it very similar to the medieval theatre with its simplicity of staging originated from liturgical drama. It is stated that here one has a sacred theatre, which has not a referential but a performative function to create a real world akin to the sacramental Real Presence, represented by the image of Grail. From the philosophical point of view, the religious longing for Grail can be treated as Derridian messianicity.
Keywords: theatre; history; image; time; place; Real Presence